Recent Advances in Polysaccharides Derived from the Genus Panax : Preparation Strategies, Structural Profiles, Functional Properties and Structure-Activity Relationships - Bu, Yingxuan; Liu, Yupeng; Zhu, Lingyan; Gan, Xiaona; Jiang, Shenggui; Zhang, Xiaoyu; Dilixiati, Munisa; Bai, Muwei; Zeng, Jiani; Shi, Songshan; Li, Tingzhao; Li, Bo; et al. (Journal of agricultural and food chemistry, 2024)
Plants from the genus have significant medicinal and nutritional benefits. Many species are traditionally used in Chinese medicine and have gained popularity as food and health products because of their tonic effects and high safety. Their key bioactive components include polysaccharides, which are hydrophilic biomolecules that have demonstrated significant potential in the food and pharmaceutical industries because of their multiple health-promoting qualities, such as immunomodulatory, antitumor, antiaging, blood glucose and blood lipid regulation, antiviral, hepatoprotective, and gastrointestinal protective properties. Additionally, polysaccharides are abundant in health products made from the genus , such as energy drinks and herbal teas. However, compared with more extensively studied components, such as ginsenosides and saponins, polysaccharides from the genus (GPPs) have been the subject of relatively limited research. This review provides a comprehensive overview of the extraction and purification technology, structural characteristics, biological activities, applications, and structure-activity relationships of GPPs. Ultimately, this information establishes a theoretical foundation for the further development and application of GPPs in nutrition and medicine.